Association between depressive symptoms and pericardial fat in healthy older men and women - Natalie Ella Miller; Andrew Steptoe (Scientific Reports, 2022)
Abstract Depressive symptoms are associated with increased risk for cardiovascular disease (CVD), and inflammation may contribute to this relationship. Pericardial fat, a highly metabolically active fat depot, is implicated in the pathogenesis of CVD, but its association with depressive symptoms is unclear. This study examined the cross-sectional and longitudinal association between depressive symptoms and pericardial fat over a three-year period. Participants were 543 healthy men and women (mean age = 62.9 years) without history or objective signs of coronary heart disease from the Whitehall II cohort. In men, depressive symptoms were positively associated with pericardial fat at baseline after adjustment for sociodemographics, waist to hip ratio and conventional cardiovascular risk factors. Inflammation, indexed by plasma interleukin 6 concentration, accounted for 17% of this association. Longitudinally, depressive symptoms did not predict pericardial fat three years later in men once baseline levels of pericardial fat were accounted for. No significant associations between depressive symptoms and pericardial fat were found in women. Overall, our findings suggest that greater pericardial fat might be a mechanism by which depressive symptoms are associated with increased risk for CVD in men, and inflammation may also lie on this pathway.